RECIST 1.1 versus mRECIST for assessment of tumour response to molecular targeted therapies and disease outcomes in patients with hepatocellular carcinoma: a systematic review and meta-analysis - Yao Yang; Yuping Bai; Hongli Yu; Qiang Zhu; Xiaoyu Xie; Yuemin Feng (BMJ Open)
Objectives Response Evaluation Criteria in Solid Tumours version 1.1 (RECIST 1.1) and modified RECIST (mRECIST) are commonly used to assess tumour response. Which one is better to evaluate efficacy after molecular targeted therapies in hepatocellular carcinoma (HCC) patients is still controversial. A systemic review was performed to compare the objective response rate (ORR) and disease control rate (DCR) and a meta-analysis was conducted to compare the correlation between objective response and overall survival (OS).Design Systematic review and meta-analysis using the Grading of Recommendations Assessment, Development and Evaluation approach.Data sources EMBASE, PubMed, Web of Science and Cochrane Library were searched through 31 December 2021.Eligibility criteria We included studies assessing the efficacy of molecular targeted therapy for HCC according to both RECIST 1.1 and mRECIST.Data extraction and synthesis Two investigators extracted data independently. The consistency between RECIST 1.1 vs mRECIST is measured by the k coefficient. HRs with corresponding 95% CIs were used for meta-analysis.Results 23 studies comprising 2574 patients were included in systematic review. The ORR according to mRECIST is higher than RECIST1.1 (15.9% vs 7.8%, p<0.001). The DCR is similar (68.4% vs 67.2%, p=0.5). The agreement of tumour response is moderate for objective response (k=0.499) and perfect for progressive disease (k=0.901), calculated from 8 studies including 372 patients. OS was significantly longer in response group than non-response group according to mRECIST (HR 0.56, 95% CI 0.41 to 0.78, p=0.0004) calculated from 7 studies including 566 patients, however, the RECIST1.1 could not distinguish the OS well (HR 0.68, 95% CI 0.44 to 1.05, p=0.08). Subgroup analusis by type of treatment was conducted.Conclusions mRECIST may be more accurate than RECIST 1.1 in assessing ORR after molecular targeted therapies in HCC patients and can better assess the prognosis. However, the performance of both criteria in assessing disease progression is identical.PROSPERO registration number CRD42020200895.Ethics approval Ethics approval is not required in this meta-analysis.